2022
DOI: 10.1021/acsanm.2c01388
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Supported Ag Nanoparticle Aerogel for Electrocatalytic Hydrogenation of 5-(Hydroxymethyl)furfural to 2,5-Hexanedione Under Acidic Conditions

Abstract: A growing interest in the electrochemical conversion of biomass-derived compounds is attributed to the extremely high sustainability of this process, which has the potential to generate value-added products and renewable electricity from biowastes. The design and synthesis of a high surface area-interconnected porous network of metal nanomaterials are desirable for their application in the field of catalysis. In this work, the synthesis of the carbon-supported Ag nanoparticle aerogel (Ag–aerogel–CN x ) for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…4), which consisted of the processes of hydrogenolysis and Clemmensen reduction as well as furan ring-opening. In addition to the work of Choi et al , 52 similar mechanisms have been reported by Barman et al (with carbon-supported Ag nanoparticle aerogel as the electrode) 53 and Sarno et al (with Ag/graphene as the electrode). 97 Although the reported cases on electrocatalytic reduction are still very scarce, this is a highly promising route to replace thermocatalysis.…”
Section: Efficient Synthesis System Of Linear Diketones From Biomasssupporting
confidence: 67%
See 2 more Smart Citations
“…4), which consisted of the processes of hydrogenolysis and Clemmensen reduction as well as furan ring-opening. In addition to the work of Choi et al , 52 similar mechanisms have been reported by Barman et al (with carbon-supported Ag nanoparticle aerogel as the electrode) 53 and Sarno et al (with Ag/graphene as the electrode). 97 Although the reported cases on electrocatalytic reduction are still very scarce, this is a highly promising route to replace thermocatalysis.…”
Section: Efficient Synthesis System Of Linear Diketones From Biomasssupporting
confidence: 67%
“…9. 53 In addition, linear diketones have also been widely reported for the synthesis of N-substituted pyrroles. These pyrroles are often deemed as indispensable five-membered N-containing heterocyclic backbones for the preparation of many commercial drugs with examples including aloracetam (for Alzheimer's disease), atorvastatin (for cardiovascular disease), etc.…”
Section: For Pharmaceutical Chemical Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…156 For example, a high Faradaic efficiency of 78% and a selectivity of 77% were observed for the conversion of HMF to 2,5-hexanedione on Ag-aerogel-CN x at −1.1 V versus Ag/AgCl in 0.5 mol L −1 H 2 SO 4 . 157 In addition to these, DHMTHF can also be produced through the intermediate of DHMF. Li et al synthesized the use of a bifunctional Pd/VN (VN-3D vanadium nitride) hollow nanosphere electrode for the simultaneous electrocatalytic oxidation and electrocatalytic hydrogenation of HMF at both F I G U R E 10 Reaction pathway of electrocatalytic hydrogenation of 5-HMF.…”
Section: Electrocatalytic Hydrogenation Of Hmfmentioning
confidence: 99%
“…Recently, metal aerogels including gold aerogels (GAs) have aroused broad interest in catalysis, adsorption, electrochemistry, biocompatibility devices, sensors, and various other fields (10)(11)(12)(13)(14)(15)(16)(17). Three main routes to the preparation of metal aerogels have been developed previously, including (i) reducing metal compound aerogel (18)(19)(20), (ii) freezing-drying metal nanowire hydrogel (21)(22)(23), and (iii) using self-assemble technology to collect metal NPs (10,(16)(17)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%